Projection Formulae

Projection formulae is the length of any side of a triangle is equal to the sum of the projections of other two sides on it.

In Any Triangle ABC,

(i) a = b cos C + c cos B

(ii)  b = c cos A + a cos C

(iii) c = a cos B +  b cos A

Proof:   

Let ABC be a triangle. Then the following three cases arises:

Case I: If ABC is an acute-angled triangle then we get,

           a = BC = BD + CD                                              ………………………… (i)

Now from the triangle ABD we have,

cos B = BD/AB   

⇒ BD = AB cos B

⇒ BD = c cos B, [since, AB = c]

Again, cos C = CD/AC  

⇒ CD = AC cos C 

⇒ CD = b cos C, [since, AC = b]

Projection Formulae

Now, substitute the value of BD and CD in equation (i) we get,

        a = c cos B + b cos C         

Note: We observe in the above diagram BD and CD are projections of AB and AC respectively on BC.


Case II: If ABC is an acute-angled triangle then we get,

            a = BC = CD - BD                                           ………………………… (ii)

Now from the triangle ADC we have,

cos C =  CD/AC   

⇒ CD = AC cos C

⇒ CD = b cos C, [since, AC = b]

Again, cos (π - B) = BD/AB  

⇒ BD = AB cos (π - B)

a = b cos C + c cos B

⇒ BD = -c cos B, [since, AB = c and cos (π - θ) = -cos θ]

Now, substitute the value of BD and CD in equation (ii) we get,

       a = b cos C - (-c cos B)

⇒ a = b cos C + c cos B


Case III: If ABC is a right-angled triangle then we get,

             a = BC                                              ………………………… (iii)

and cos B =  BC/AB   

⇒ BC = AB cos B

⇒ BC = c cos B, [since, AB = c]

Now, substitute the value of BC in equation (iii) we get,

       a = c cos B

⇒ a = c cos B + 0

b = c cos A + a cos C

⇒ a = c cos B + b cos C, [since C = 90° ⇒ cos C = cos 90 = 0] 

Therefore, in any triangle ABC we get, a = b cos C + c cos B

Similarly, we can prove that the formulae b = c cos A + a cos C and c = a cos B + b cos A.


Solved problem using the projection formulae:

If the area of the triangle ABC be ∆, show that,
                       b\(^{2}\) sin 2C + c\(^{2}\) sin 2B = 4∆.

Solution:

b\(^{2}\) sin 2C + c\(^{2}\) sin 2B

= b\(^{2}\) 2 sin C cos C + c\(^{2}\) ∙ 2 sin B cos B

= 2b cos C ∙ b sin C + 2c cos B ∙ c sin B

= 2b cos C ∙ c sin B + 2c cos B ∙ c sin B, [Since, a/sin B = c/sin C b sin C = c sin B]

= 2c sin B (b cos C + c cos B)

= 2c sin B ∙ a [Since, we know that, a = b cos C + c cos B]

= 4 ∙ ½ ac sin B

= 4∆.                        Proved.





11 and 12 Grade Math

From Projection Formulae to HOME PAGE




Didn't find what you were looking for? Or want to know more information about Math Only Math. Use this Google Search to find what you need.